Insulin-like growth factor 1 injection changes gene expression related to amino acid transporting, complement and coagulation cascades in the stomach of tilapia revealed by RNA-seq - Zhong, Huan; Lou, Chenyi; Ren, Bingxin; Zhou, Yi (Frontiers in Immunology, 2022)
Insulin-like growth factor 1 (IGF-1) is a key hormone that regulates fish growth. It acts on a variety of organs and regulates multiple signaling pathways. In order to explore the specific effects of IGF-1 on fish nutrient absorption, immune system, and other functions, the present study investigated the transcriptional changes of stomachs in tilapia by IGF injection. The tilapias were divided into two groups which were injected with saline (C group) and IGF-1 (2 μg/g body weight) (I group), respectively. After three times injections, the stomachs from the tested tilapias were collected 7 days post the first injection and the transcriptomes were sequenced by Illumina HiSeqTM 2000 platform. The results showed that a total of 155 DEGs were identified between C and I groups. By gene ontology (GO) enrichment analysis, two GO terms related to absorption function were enriched including organic acid transport, and amino acid transport which contained 6 functional DEGs. The Kyoto Encyclopedia of Genes and Genomes (KEGG) enrichment analysis suggested that Staphylococcus aureus infection, as well as complement and coagulation cascades pathways were enriched and contained 6 DEGs. Taken together, the present study indicated that IGF-1 injection altered gene expression related to amino acid transporting, complement and coagulation cascades which provides a promise immunopotentiation therapy by IGF-1 in digestive tract of tilapia.